Clinical, CBCT and Histological Analysis of a Florid Cemento-Osseous Dysplasia with Co-Occurrence of Simple Bone Cyst in the Mandible: A Case Report - Antoine Berberi (Shiraz University of Medical Sciences, 2024)
Cemento-osseous dysplasia (COD) is classified, by the World Health Organization as a benign fibro-osseous lesion related to the tooth and periapical area of the jaws and is considered as a benign reactive process appearing from the apical periodontium in close relation with the apices of teeth. Usually, it is asymptomatic, discovered accidentally, and affecting particularly middle-aged African women. There are four subtypes distinguished of the lesion: periapical (PCOD), focal (FCOD), florid (FLCOD) and familial florid cemento-osseous dysplasia (FFLCOD). Pseudocysts found in the jaws go by various names, including solitary bone cyst, traumatic bone cyst, or simple bone cyst (SBC). These two pathologies have been reported separately; however, their co-occurrence remains rare and the first case of FLCOD with co-occurrence of SBC was reported by Melrose et al. in 1976 and later a few cases been reported in the literature. The aim of this report is to describe a case of a 46-year-old oriental female diagnosed with FLCOD with co-occurrence of SBC. Under local analgesia, a surgical exploration of the cyst was performed. In addition, a biopsy with a trephine was done in the region of missing right first mandibular molar. Based on the patient clinical, radiographic, and histological findings, a diagnosis of FLCOD was made in co-occurrence with a mandibular SBC. An examination of another female family member unveils a distinctive case, and the familial factor has been ruled out. No further treatment was planned and only follow-up was suggested.